1992
DOI: 10.1128/aac.36.4.788
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Vibrio cholerae cells with beta-lactam antibiotics: emergence of resistant cells at a high frequency

Abstract: Unlike other gram-negative enteric bacteria, Vibrio cholerae cells were equally susceptible to penicillin and ampicillin and in general more susceptible than Escherichia coli to most of the beta-lactam antibiotics. The turbidity of penicillin-treated cultures continued to increase exponentially for about 3 h, although the cell viability declined rapidly within 30 min of penicillin addition. Prolonged treatment with beta-lactam antibiotics produced cells resistant to these antibiotics. A fluctuation test indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Thus, these cells are highly sensitive to a wide range of chemicals. 31) Indeed, V. cholerae possess the highest mean values of susceptibility to ten different plant polyphenols. 32) Taken together, our results indicate that these cell surface features of V. cholerae may be causative of the critical susceptibility to honokiol and magnolol compared to other pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these cells are highly sensitive to a wide range of chemicals. 31) Indeed, V. cholerae possess the highest mean values of susceptibility to ten different plant polyphenols. 32) Taken together, our results indicate that these cell surface features of V. cholerae may be causative of the critical susceptibility to honokiol and magnolol compared to other pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the murein network plays a significant role in determining the stability of cell surfaces of bacteria. Several studies have indicated the delicate nature of the murein networks of V. cholerae cells (4,13,25). It is a real mystery how these cells survive in the human intestine.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, several studies have indicated the fragile nature of the murein networks of V. cholerae cells (4,13,25). In E. coli, the peptidoglycan network is thin but "more than a monolayer" (10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations